Dosage Effects of Lactococcus lactis ssp. lactis 2 as a Probiotic on the Percentage of Carcass, Abdominal Fat Content and Cholesterol Level in Broilers - Mujnisa , A.; Gustina, Lailya; Natsir, Asmuddin; Hasan, Syamsuddin (International Journal of Poultry Science, 2018)
Objective: This study was conducted to determine the dosage effects of the lactic acid bacteria (LAB) Lactococcus lactis ssp. lactis 2 as a probiotic on the percentage of carcass, abdominal fat content and cholesterol level in broilers. Methodology: Lactococcus lactis ssp. lactis 2 was isolated from broiler faeces. The microbe count was 1.3×108 CFU g–1. The treatments in this study consisted of the following groups, P0: Without administration of the probiotic, P1: With the administration of 0.01% zinc bacitracin antibiotic, P2: With the administration of Lactococcus lactis ssp. lactis 2 probiotic at a dose of 0.5% (6.5×108 CFU kg–1), P3: With the administration of Lactococcus lactis ssp. lactis 2 probiotic at a dose of 1% (1.3×109 CFU kg–1) and P4: With the administration of Lactococcus lactis ssp. lactis 2 probiotic at a dose of 1.5% (1.95×109 CFU kg–1). Results: This study showed that administration of the LAB Lactococcus lactis ssp. lactis 2 with a 0.5% (6.5×108 CFU kg–1), 1% (1.3×109 CFU kg–1) and 1.5% (1.95×109 CFU kg–1) dose did not influence abdominal fat content, however, probiotic administration reduced cholesterol in breast meat and thigh meat and reduced fat in breast meat compared to the antibiotic and control treatments. Administration of Lactococcus lactis ssp. lactis 2 probiotic at a 1.5% dose (1.95×109 CFU kg–1) resulted in a higher percentage of carcass and lower percentage of thigh meat cholesterol compared to the 0.5% (6.5×108 CFU kg–1) and 1% (1.3×109 CFU kg–1) doses. Conclusion: The administration of Lactococcus lactis ssp. lactis 2 did not affect abdominal fat content but reduced breast meat cholesterol and thigh meat cholesterol. The 1.5% dose (1.95×109 CFU kg–1) produced a higher percentage of carcass and lower thigh meat cholesterol than did the other doses.